Optimization of reaction parameters for the electrochemical oxidation of lidocaine with a Design of Experiments approach. (20th July 2015) - Gul, Turan; Bischoff, Rainer; Permentier, Hjalmar P.
Highlights: A two-step DOE strategy is efficient to optimize EC drug metabolite synthesis A glassy carbon electrode is best for production of N-dealkylated lidocaine High pH (12) and potential (1.5 V) favor synthesis of the N-dealkylation product N-dealkylation reaction is completely blocked at a solvent pH lower than 1.5 Abstract: Identification of potentially toxic oxidative drug metabolites is a crucial step in the development of new drugs. Electrochemical methods are useful to study oxidative drug metabolism, but are not widely used to synthesize metabolites for follow-up studies. Careful optimization of reaction parameters is important for scaling up the electrochemical synthesis of metabolites. In the present study, lidocaine was used as a drug compound in order to optimize electrochemical reaction parameters employing a design of experiments approach to improve the yield of N-dealkylated lidocaine, a major in vivo metabolite. pH and electrode material were found to have a major effect on the final yield.